2017
DOI: 10.1002/jcb.26470
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory milieu cultivated Sema3A signaling promotes chondrocyte apoptosis in knee osteoarthritis

Abstract: Osteoarthritis (OA) is the leading degenerative joint disease and featured by articular cartilage destruction, where chondrocyte apoptosis plays a critical role. Semaphorin-3A (Sema3A) has been implicated in OA chondrocyte physiology. In this study we aimed to uncover how Sema3A signaling is regulated in chondrocytes and investigate its role in OA chondrocyte survival. Here, we report that Sema3A and its receptor neuropilin-1 (Nrp1) are synchronously upregulated in cartilage chondrocytes of knee OA patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…In ATDC5 cells, Sema3A induced apoptosis in a phosphatidylinositide 3-kinase/protein kinase B (PI3K/PKB)-dependent manner. In human chondrocytes from OA patients, Sema3A inhibited the VEGF 165 -induced chondrocyte cloning, a process involved in the repair of the damaged cartilage [66,67]. These results suggest that Sema3A inhibition could be an interesting therapeutic target for the treatment of OA.…”
Section: Osteoarthritismentioning
confidence: 99%
“…In ATDC5 cells, Sema3A induced apoptosis in a phosphatidylinositide 3-kinase/protein kinase B (PI3K/PKB)-dependent manner. In human chondrocytes from OA patients, Sema3A inhibited the VEGF 165 -induced chondrocyte cloning, a process involved in the repair of the damaged cartilage [66,67]. These results suggest that Sema3A inhibition could be an interesting therapeutic target for the treatment of OA.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Articular chondrocytes are derived from mesenchymal stem cells and produce various extracellular matrix proteins (ECMs) such as proteoglycans and type II collagen, and function in shock absorption and enabling smooth movement of joints. Mild articular cartilage damage can repair itself due to chondrocytes’ regenerative activities such as chondrocyte cloning regulated by reversion-inducing cysteine-rich protein with Kazal motifs (RECK) 2,3 and semaphorin 3A 46 . However, if articular cartilage damage covers a large area or occurs continuously, repair is no longer possible due to the limited proliferation and repair capacity in chondrocytes, and damage becomes irreversible, leading to osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…A similar complexity for neuronal regulation of skeletal cell differentiation and function is observed for certain neurotransmitters (such as leptin and NPY) mediated through the activation of central receptors different from those in peripheral nerves (23,91,113,117). These neuronal signals also regulate physiological and pathological conditions of cartilage by affecting chondrocyte proliferation, secretion, adhesion and terminal differentiation (21,95,99,107,124) (Fig. 3).…”
Section: Discussionmentioning
confidence: 76%
“…Gomez et al (103) reported that Sema3A and Plexin A2 mRNA were expressed in the MC615 mouse chondrogenic cell line before the onset of neurovascular invasion during endochondral ossification. In OA cartilage, Sema3A and its receptor Nrp1 were found to be upregulated (21,107). Okubo et al (21) first described that Sema3A functions competitively or cooperatively with VEGF-165 in modulating chondrocyte cloning by binding to the common receptor Nrp-1.…”
Section: Semaphorin 3a In Bone and Cartilage Metabolismmentioning
confidence: 99%
See 1 more Smart Citation